PHASE BOOSTER DEVICE WITH SINGLE-PHASE HIGH FREQUENCY LINK - Klimash, V. S.; Vlasievskyi, S. V.; Konstantinov, O. M. (Science and Transport Progress, 2007)
The device is intended for compensating the reactive capacity of circuit with simultaneous stabilization of the loading voltage. It includes a high-frequency single-phase transformer which is included between two converters. One of the converters is fitted with ad.c.link and raises frequency above that of the circuit, and the other one – with a direct communication, and lowers the frequency down to the frequency of circuit.